Natural substrates and amphipods epibionts contaminated by microplastic - Sorrentino, Rayane; Senna, André Resende de (Acta Scientiae et Technicae, 2023)
Amphipods inhabit microhabitats that protect them against predation, provide nutrition and an area for reproduction and development. However, the compounds of the ecosystem are impacted by the presence of microplastics (MPs), which are a threat to marine communities. Since the organisms interact with and ingest/filter the different quantities of MPs, and may make it available to the associated epibionts, three natural substrates (algae, sponges, and ascidians) were sampled to compare the number of MPs in them and in their associated amphipods. This study was conducted on rocky shores from Rio de Janeiro (Brazil), differently from other studies that have been focused on experimental tests. The samples were submitted to density separation to extract the microplastics and acid degradation to access MP in amphipods. Algae retained a greater concentration of MPs as a sink of particles, as well as its associated amphipods. Sponges and ascidians have different mechanisms to filter water, which influences the MPs accumulation in amphipods. Those associated with sponges and ascidians had fewer microplastic particles. This is the first study comparing the retention of MP in different natural substrates and their amphipod epibionts, which gives information about microplastic contamination in these microhabitats and their associated organisms.